Genitourinary infections as a risk factor for preterm prelabour rupture of membranes: a hospital based case control study - D’souza, Aparajita Sophia; Gupta, Garima; Mahindru, Divya; Walia, Moneet; Katumalla, Francis Sridhar; Goyal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm Prelabour Rupture of Membranes (PPROM) is a leading cause of maternal and neonatal morbidity and mortality. The objective of our study was to bring forward the association between genitourinary infections and PPROM in Indian scenario. Methods: This retrospective case-control study was conducted in the Department of Obstetrics and Gynecology, in a tertiary referral teaching hospital in Punjab. A total of 150 women were evaluated for genitourinary infections and their association with PPROM. Cases group 1 (n=75) included pregnant females with diagnosis of PPROM based on history and vaginal examination. Control group 2 (n=75) included pregnant women admitted to labour room at 37 completed weeks of gestation or more and with no history of PPROM. The control group was matched to case group with respect to age and parity. Case to control ratio was taken as 1:1. A multivariate analysis was used to find the association between PPROM and genitourinary infections. Microsoft Excel and the Statistical Package for the Social Sciences (SPSS), Version 21 were used for data analysis. A P value of <0.05 was determined to be statistically significant. Results: In our study genitourinary infections were seen in 16 women in Case Group 1 (21.3%), compared to 7 women in Control Group (9.3%). Genitourinary infections were associated significantly with PPROM (p 0.02) (odds ratio [OR], 2.618; 95% Confidence interval [CI], 1.021-7.239). Conclusions: Screening for genitourinary infections should be considered especially in high risk cases. Early recognition and prompt treatment of genitourinary infections is the key to optimize the maternal and fetal outcome in PPROM.